American Social and Family Relationship Aspects Found In Fitzgerald’s `The Great Gatzby` Novel and Its Application in English Speaking Class - Triana, Juita (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
Language and culture are closely related to each other. Learning a language should be_ also completed learning its culture. In communication, difficulty or misunderstanding usually occurs because of the lack of cultural understanding. In line with this, to be able to speak English and interact culturally especially with the English native speakers, students of English should learn the culture of them. This writing is under a research with the objectives of finding some of the culture components especially on the social and family relationship aspects found in Fitzgerald’s The Great Gatsby novel and its application in Speaking Class of English Department. It is a descriptive qualitative research. In conclusion, in the novel, it is found that in American social relationship, the people create nice relationship in which friendliness, informality, and equality marks are involved. In family relationship, Americans seem keeping their good relationship among family members by paying attention to one another. As the application in teaching speaking class, the findings can be good sources for doing some activities of learning some expressions and practicing role play based on the story of the novel. It can facilitate English students to improve their English speaking, especially in the communication with the English native speakers, in good cultural awareness.